Edukasi Pentingnya Kesehatan Reproduksi pada Remaja SMK Kesehatan di Kota Yogyakarta - Syarifah, Nur Yeti; Muryani, Muryani (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2025)
The adolescent reproductive health program is a service effort to help adolescents achieve good reproductive health status through the provision of information, counseling services, and life skills education. The existence of advocacy institutions, education, and reproductive health consultations for adolescents is currently limited in reach, resulting in minimal protection and assistance to realize adolescent reproductive rights. This community service aims to help the government improve the level of reproductive health in adolescents through education on the importance of maintaining adolescent reproductive health. The method we use is counseling in the form of education and counseling or in-depth discussions on the problems facing adolescents. The results obtained are based on a population of 40 adolescents from the Binatama Health Vocational School with the largest number of respondents being adolescent girls, amounting to 23 respondents